2022
DOI: 10.19160/e-ijer.1117470
|View full text |Cite
|
Sign up to set email alerts
|

Psikolojik Danışmanlar için Kişilerarası Stres Ölçeği’nin Türk Kültürüne Uyarlanması

Abstract: Considering that the therapeutic relationship and therapeutic conditions are inseparable conditions for the counseling process, it is important to bring a scale to the Turkish literature to examine the interpersonal stress experienced by counselors during the counseling process. In this research, the scale adaptation process from one language to another language was carried out. In this context, validity and reliability studies were carried out in 4 different samples. As a result of the research, it was seen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The study proposes using mindfulness-based tools, which possess great value in terms of helping principals to achieve well-being and reduce their stress levels. A study by Kurtulus et al (2023) found that health care employees who have a better balance between their work and personal lives tend to experience higher levels of psychological well-being. Furthermore, psychological well-being plays a mediating role between social support and work-life balance.…”
Section: Work-life Balance and Well-beingmentioning
confidence: 99%
“…The study proposes using mindfulness-based tools, which possess great value in terms of helping principals to achieve well-being and reduce their stress levels. A study by Kurtulus et al (2023) found that health care employees who have a better balance between their work and personal lives tend to experience higher levels of psychological well-being. Furthermore, psychological well-being plays a mediating role between social support and work-life balance.…”
Section: Work-life Balance and Well-beingmentioning
confidence: 99%
“…Bireyin sosyal ortamdaki etkileşimi ve tercihleri neticesinde var olduğu ortam iç dünyasındaki sahip olduğu aidiyet mekanizması değişir (Alptekin, 2011). Aidiyet gereksinimi ergenlik çağında toplumun kabul gördüğü çerçevede karşılanmaz ve doyuma ulaştırılamazsa sonucunda sakıncalı davranışları da beraberinde getirebilir (Duru, 2007). Kişi aile ortamında aidiyet gereksinimini karşılayamazsa farklı sosyal ortamlarda bu duyguyu giderebilmek için arayışa başlar (Güneş, 2016).…”
Section: Aile Aidiyetiunclassified
“…Aidiyet duygusu bireyin kendisiyle veya çevresindeki bireylerle birbirlerine verdikleri değer ve önem sonucu aynı ortamda olmanın neticesindeki yükümlülükleri barındırır. Bu yükümlülüklerin karşılıklı bir şekilde gerçekleştirilmesi olarak değerlendirilebilir (Duru, 2007). Birey bir topluma ait olma gereksinimini toplumsallaşma sürecinde fark eder (Aksan ve Alptekin, 2009).…”
Section: Aile Aidiyetiunclassified